Distributed Consensus Observer for Multiagent Systems With High-Order Integrator Dynamics - Zuo, Zongyu; Defoort, Michael; Tian, Bailing; Ding, Zhengtao (IEEE transactions on automatic control, 2020)
This article presents a distributed consensus observer for multiagent systems with high-order integrator dynamics to estimate the leader state. Stability analysis is carefully studied to explore the convergence properties under undirected and directed communication, respectively. Using Lyapunov functions, fixed-time (resp. finite-time) stability is guaranteed for the undirected (resp. directed) interaction topology. Finally, simulation results are presented to demonstrate the theoretical findings.